METHODS FOR PROCESSING GREENHOUSE RAW MATERIALS - Umarov Isroil; F.Dadaxanov (Journal of new century innovations, 2023)
Abstract. The properties of Sera raw materials, its support as a binding material, the preparation of concrete and the comparison of cerobeton with Portland-based concrete were carried out. Also, in the field of zero betting, the possibilities for the production of serotonin using serotonin were analyzed.